Higher-Order Commutators of Parametric Marcinkiewicz Integrals on Herz Spaces with Variable Exponent. (1st November 2018) - Wang, Hongbin; Yan, Dunyan
Abstract : LetΩ ∈ L s ( S n - 1 ) fors ⩾ 1 be a homogeneous function of degree zero andb be BMO functions. In this paper, we obtain some boundedness of the parametric Marcinkiewicz integral operatorμ Ω ρ and its higher-order commutator[ b m, μ Ω ρ ] on Herz spaces with variable exponent.